Les apocryphes - textes concurrentiels du Nouveau Testament - Rebell, Walter (Apocrypha, 1996)
Every text acts in a particular way on its reader ; comparing the Apocryphon of John, the Epistle of Barnabas and the Gospel of the Hebrews with New Testament texts, the author analyses this impact and concludes that a certain number of apocryphal texts functioned - or might have functioned - in the same way as canonical texts.